Relationship Between Street Hawking, Study Habit and Academic Performance of Upper Basic School Students in Federal Capital Territory, Abuja, Nigeria - Gidado, Bello Kumo; Esomojumi, Rosemary Taiwo (Journal of Education and Practice, 2024)
Purpose: This study investigated the relationship between street hawking, study habits and academic performance of Upper Basic School Students in Federal Capital Territory, Abuja, Nigeria. Methodology: The research design adopted for the study was descriptive survey design. A total of 43,922 Upper Basic School Students comprises the population. Krejcie and Morgan (1970), was used in drawing the sample of 240 students. A Self-structured questionnaire was used to collect data from the respondents. The data collected was subjected to statistical analysis based on the six null hypotheses. A multiple correlation regression, an analysis of variance, t- test and Pearson correlation coefficient was used in analysing the hypotheses. Findings: The findings from the study showed that, there is no significant relationship between street hawking, study habits and academic performance of students in Federal Capital Territory, Nigeria, it further shows that there is no significant relationship between street hawking and study habits and that upper basic school students do not differ significantly in their study habit on the basis of gender. The results further revealed that there is no significant relationship between street hawking and academic performance of students in Upper Basic Schools, and that Students differ significantly in their academic performance based on different hawking time. It was further discovered that upper basic school Students do not differ significantly in their academic performance because of those engaged in street hawking and students who do not. Unique Contribution to Theory, Policy and Practice: It was recommended that parents should allow their ward hawk only after school and hours of hawking should be limited and as well monitored. The results of this have significantly address the long-standing view that students who are engaged in street hawking tent to perform poorly, academically. The non-relation obtained in this study has further revealed the need to look at other environmental factors that may likely influence academic performance of school children street hawkers. Further study may still be needed to reconcile the differences in performances in performances between students engaged in street hawking and those who do not.